Heterostructures: Light Driven Active Transition of Switching Modes in Homogeneous Oxides/Graphene Heterostructure (Adv. Sci. 11/2019). Issue 11 (4th June 2019) - Chen, Xiaoli; Zeng, Kelin; Zhu, Xin; Ding, Guanglong; Zou, Ting; Zhang, Chen; Zhou, Kui; Zhou, Ye; Han, Su‐Ting
Abstract : In article number1900213, Ye Zhou, Su‐Ting Han, and co‐workers demonstrate a photo‐induced transition from oxygen vacancy filament to metal filament in the heterostructure of titanium oxides/graphene. A voltage controlled negative differential resistance effect is also obtained. This will provide significant insight into the design and manipulation of memristive devices based on heterostructured materials.